Is There a Case for Quarantine? Perspectives from SARS to Ebola - Barbisch, Donna; Koenig, Kristi L; Shih, Fuh-Yuan (Disaster medicine and public health preparedness, 2015)
Quarantine has been used for centuries in an effort to prevent the introduction, transmission, and spread of communicable diseases. While backed by legal authority, the public and even the health care worker community’s understanding of the term is murky at best and scientific evidence to support the use of quarantine is frequently lacking. The multiple interpretations and references to quarantine, the inconsistent application of public health quarantine laws across jurisdictional boundaries, and reports of ineffectiveness are further complicated by associated infringement of civil liberties and human rights abuses. Given the need to balance public safety with human rights, we must be more precise about the meaning of quarantine and consider the efficacy and negative secondary effects resulting from its implementation. This article explains quarantine terminology and then uses a case study from Taiwan during the 2002–2003 severe acute respiratory syndrome (SARS) outbreak to illustrate the key principles associated with quarantine measures taken during the 2014 Ebola outbreak and the potential hazards that can arise from quarantines. Finally, we provide a quarantine and isolation decision tree to assist policy makers and public health officials in applying medically defensible, outcomes-based data and legal authorities to optimize management of emerging infectious diseases. (Disaster Med Public Health Preparedness. 2015;9:547–553)